MENUMBUHKEMBANGKAN WIRAUSAHA BERBASIS INDUSTRI KREATIF FESYEN BAGI WARGA PEDESAAN DENGAN MEMANFAATKAN FLORA PADA PRAKTIK PENYEMPURNAAN KAIN DENGAN TEKNIK ECO PRINT - CUCU SUTIANAH (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Pasir Panjang village is one of the villages that produce natural resources in the form of wood, agriculture and other agricultural products, and has the potential for the community to become entrepreneurs. The village is located in Manonjaya District, Tasikmalaya Regency, West Java Province. And Nagarasari Village, Cipedes District, Tasikmalaya City is a very productive area in making batik, but in making batik it still uses chemicals. Efforts to tackle unemployment for productive age in rural areas, namely by increasing and increasing the number of entrepreneurial-minded activities. Most of the entrepreneurial activities are also very helpful in fulfilling the needs of society. One way to reduce the unemployment rate, Because youth are expected to be able to become educated young entrepreneurs who are able to start their own businesses. To develop a business, entrepreneurs must carry out a full strategy such as conducting training in the manufacture of goods and services by utilizing natural resources of flora around rural communities. The results of the independent entrepreneurship training for youth at the Taruna Train and PKK Women in Pasirpanjang Village, Manonjaya District, Tasikmalaya Regency and Nagarasari Village, Cipedes Koata Tasikmalaya District, one of which is a form of exercise in perfecting plain cloth using leaves and flowers and natural dyes derived from growing flora. in rural communities, known as Eco print.